1987
DOI: 10.1017/s0022112087002532
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bödewadt flow

Abstract: Boundary-layer transition over a stationary disk in rotating flow is studied experimentally. Circular waves are observed in the boundary layer occurring on an end disk of a cylindrical cavity during impulsive spin-down to rest. The transient flow evolves into a quasi-steady regime that exhibits the properties of the Bödewadt flow. The circular waves develop in that flow. The critical Reynolds number Re = r(Ω/v)½ is determined from frequency and wavelength measurements to be about 25. The corresponding dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 22 publications
10
61
2
Order By: Relevance
“…Many studies have been performed to reveal the similarities in the stability characteristics across the entire BEK class (see, for example, the theoretical and experimental studies discussed in papers [9][10][11][12][13][14] for the Bödewadt layer; papers [15,16] for the Ekman layer; and papers [17][18][19][20] for the von Kármán flow). These studies have shown the existence of two main flow instability mechanisms, commonly referred to as the Type I and the Type II modes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed to reveal the similarities in the stability characteristics across the entire BEK class (see, for example, the theoretical and experimental studies discussed in papers [9][10][11][12][13][14] for the Bödewadt layer; papers [15,16] for the Ekman layer; and papers [17][18][19][20] for the von Kármán flow). These studies have shown the existence of two main flow instability mechanisms, commonly referred to as the Type I and the Type II modes.…”
Section: Introductionmentioning
confidence: 99%
“…For disk boundary layer problems, this generally means that the finite disk needs to be shrouded by a cylinder. Savaş 20,21 conducted a series of experiments where initially a regime corresponding to quasisteady finite Bödewadt flow exists. The initial state consists of a filled circular cylinder in solid-body rotation of angular rotation rate ⍀.…”
Section: Introductionmentioning
confidence: 99%
“…Lopez and Weidman 22 repeated the experiments of Savaş, 21 reproducing the radially inward traveling circular waves in the disk boundary layer, and also simulated these states using the Navier-Stokes equations. They further showed numerically that if instead of impulsively stopping the entire cylinder, only the end walls are stopped while the cylindrical sheath continues rotating, then the development of the disk boundary layer and its inflectional instability leading to the formation of the circular waves is essentially the same, but without the large disturbances from the sidewall due to the whole flow spinning down.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, and following the pioneer work of Lingwood [9], Serre et al [11] studied theoretically and numerically the transition from convective to absolute instability of these flows. Experimentally, Savas [12,13] followed by Itoh [14,15] were the first to visualize the different waves occurring in a rotor/stator system. The complete transition diagram was then built by Schouveiler, Le Gal & Chauve [16] as function of the ratio h/δ of the cavity and of the Reynolds number Re = ΩR 2 /ν (R being the radius of the disk).…”
Section: Introductionmentioning
confidence: 99%